Structural studies of a hemicellulose B fraction (B-2) from the cork of Quercus suber - Asensio, A (Canadian journal of chemistry, 1988)
Polysaccharide B-2 contains xylose, arabinose, glucose, galactose, 4-0-methylglucuronic acid, and rhamnose in the molar ratio of 17: 12: 12:6:4: 1. The polysaccharide has a backbone of P(1-4)- and P( 1-3)-linked glucopyranosyl, P(lk4)-linked xylopyranosyl, and (1-4)- and (1-6)-linked galactopyranosyl residues. Arabinofuranosyl, rhamnopyranosyl, and some xylopyranosyl and galactopyranosyl groups are present as nonreducing end units. Glucopyranosyluronic acid side chains are attached at 0 - 2 of some xylose residues. The anomeric configurations of the different glycosyl groups were determined by a study of the chromium trioxide oxidation of the acetylatcd polysaccharide and by nuclear magnetic reasonance spectra of the methylated polysaccharide.
Keywords: Configuration; GLC-MS (voyant); Polysaccharides